Lipocalin-2 (LCN-2) is a novel myokine that reduces lipid accumulation and induces lipolysis in adipocytes - Alsolami, Areej (2023)
Introduction LCN-2 is an acute phase protein, first identified as an adipokine secreted by adipose tissue. Contradictory experimental results show that LCN-2 is involved in pro- and anti-inflammatory states and can both increase and decrease insulin resistance. However, whilst the Lipocalin-2 protein is widely expressed in several tissues/cells, its expression has been poorly studied in skeletal muscle. Experiments in FRAME lab have demonstrated that the mRNA expression of LCN-2 is increased after exercise post 3-hr in vivo in 3 partipiants out of 6, and therefore its role in skeletal muscle following exercise needs to be investigated. We hypothesise that LCN-2 is a novel potential myokine, acting post exercise in an endocrine fashion that affects lipid metabolism. Methods Primary human myotubes were isolated from healthy volunteers and cultured to study LCN-2 expression and secretion in response to EPS stimulation and AICAR treatment. The lentiviral inducible vector pINDUCER20 was used to enable inducible overexpression of LCN-2 in human primary myotubes. Lastly, adipocytes were exposed to conditioned media (CM) derived from human myotubes that overexpress LCN-2 to study the crosstalk between muscle and adipose tissue. Results We found that LCN-2 mRNA expression was significantly upregulated in a time- dependant manner (2 h, 4 h, 16 h) by EPS (p<0.0001; 6-fold post-16 hr) and protein was secreted by human myotubes in response to 16 h of EPS (p<0.0001; 43% increase). Moreover, the level of LCN-2 secretion by myotubes increased in response to AICAR treatment for 48 h (p<0.0001; 3-fold increae). Lipid accumulation in adipocytes (3T3L-1) reduced significantly post-48 h when adipocytes (3T3L-1) were exposed to 50% CM derived from human myotubes that overexpress LCN-2 (p<0.0001; 3-fold). Moreover, a significant increase in release of glycerol (nmol/mg of cell protein) post48 h occurred when exposed to human myotube CM (p<0.001; 2- fold). Additionally, we found that ATGL protein was upregulated in response to LCN-2 containing conditioned medium (p<0.0001; ~ 4-fold). Conclusion We conclude that LCN-2 is a novel exercise-induced myokine that appears to induce lipolysis and decrease lipid accumulation in adipocytes.